Kedudukan Gugatan Rekonvensi dalam Cerai Talak dan Cerai Gugat di Peradilan Agama - Maria Rosalina; Shafira Putri Azhari; Najwa Tindaon; Chairunnisa Chairunnisa (AHKAM, 2026)
Although counterclaims have been recognized as a defendant’s formal right in civil procedural law, their position in divorce by repudiation and contested divorce cases within the Religious Courts still faces inconsistent practice, particularly due to a normative gap in the Compilation of Islamic Law. This study aims to examine the position of counterclaims in divorce by repudiation and contested divorce cases and to analyze their effectiveness as an instrument for protecting the rights of the parties. This study uses a normative legal method with statutory and conceptual approaches. Legal materials were analyzed descriptively and analytically to examine the regulation of counterclaims under the HIR and RBg and their relevance in the practice of resolving divorce cases in the Religious Courts. The results of the study show that counterclaims have an important position as a means of protecting the defendant’s rights as well as an instrument of procedural efficiency through the concept of one-stop litigation. However, their effectiveness is still hindered by normative uncertainty regarding post-divorce rights and weaknesses in the enforcement of judgments. Supreme Court Circular Number 3 of 2018, through the judge’s ex officio authority, constitutes a legal breakthrough in protecting women’s rights, but it cannot replace the active role of counterclaims as an instrument for asserting the rights of the parties. The conclusion of the study affirms that counterclaims need to be positioned as a strategic legal mechanism in resolving divorce cases in the Religious Courts. The implications of this study indicate the need for regulatory synchronization and the preparation of more comprehensive operational guidelines to ensure legal certainty, judicial efficiency, and substantive justice for the litigating parties.